Efektivitas Latihan Fisik dalam Meningkatkan Kualitas Hidup Pasien Sirosis Hati - Faljeki Kurniawan; Agung Waluyo; I Made Kariasa; Chiyar Edison (Journal of Telenursing (JOTING), 2023)
This systematic review aims to examine the effectiveness of physical exercise in improving the quality of life of liver cirrhosis patients. The author's method was to carry out a search process for relevant journals regarding the influence of physical exercise in improving the quality of life of liver cirrhosis patients. The author searched for literature using four data bases, namely; pubmed, embase, clinical key, science direct with year restrictions from 2020 - 2023. During the search process the author typed several keywords, such as: Physical therapy OR Physical exercise OR Physical activity) AND (quality of life OR Life Quality OR Health-Related Quality Of Life) AND (Liver cirrhosis OR Hepatic Cirrhosis. The results of the research, from the initial search results, resulted in 6 articles being analyzed. Of the 6 physical activity articles, The Strength Training Intervention (STRIVE), Home-Based Physical Activity, Resistance Training, were effective in improving quality life in liver cirrhosis patients. In conclusion, physical activity interventions applied to liver cirrhosis patients can improve the quality of life of liver cirrhosis patients. Keywords: Hepatic Cirrhosis, Liver cirrhosis, Physical exercise, Physical therapy, Quality of life.